Regarding Estrangement: Perceiving the Infinite in Symbol and Fusing Horizons - Robinson, Jason (My University, 2003)
The purpose of this thesis is to introduce the reader to Paul Tillich's notion of the "symbol," including "religious symbol," and Hans-Georg Gadamer's notion of the "fusion of horizons," including his notion of the "question" and "play" or "game." It introduces the pertinent aspects of Tillich's and Gadamer's literary writings as well as explains the motivation behind their respective works, namely, their different reactions to estrangement and alienation. During the explication of how Tillich's "symbol" and Gadamer's "fusion of horizons" redeem us, an examination of how each thinker works with issues of subjective and objective thinking, what it means for the question to be a priority and how these issues relate to our ontology, is made. This thesis culminates with an examination of the appropriateness and applicability of Tillich's and Gadamer's approaches to hermeneutical thinking.